The Influence of Service Quality and Customer Value on Customer Satisfaction and Its Impact on Brand Trust in the Use of the BJB Digi Mobile Application in West Java - Lingga D. Ciptha (Journal Tourism Nomic, 2025)
This study investigates the influence of service qualityand customer value on customer satisfaction and theirsubsequent impact on brand trust in the context of the BJB Digimobile banking application in West Java. Employing aquantitative approach and Structural Equation Modeling (SEM)with AMOS, data were collected from 200 active users throughpurposive sampling. The findings reveal that service quality doesnot directly affect brand trust, but exerts a significant indirectinfluence through customer satisfaction. In contrast, customervalue demonstrates both direct and indirect positive effects onbrand trust. Customer satisfaction itself is shown to moderatelyinfluence brand trust, confirming its mediating role. Theseresults underscore that improving service quality alone isinsufficient to build brand trust unless it leads to highersatisfaction. Instead, enhancing perceived customer valueemerges as a more effective strategy for fostering trust in digitalbanking services. The study contributes to digital bankingliterature by highlighting the interconnected roles of servicequality, perceived value, and satisfaction in strengthening brandtrust, particularly in underutilized mobile banking platforms.Practical implications suggest that financial service providersshould prioritize value-driven experiences to improve customerretention and trust